Polykria Milik Kita - Toekio, Soegeng (KEMADHA, 2012)
An exhibition  is basically a work culture  that  implements a combination of  creative  and  proficiency.  The  rate  of  development  is  determined  by  the offender , seeker , and the atmosphere of the times. When the cultural dynamics at  the  center  of  civilization,  including  what  came  to  pass  that  mark  the interaction dynamics of  the movement known as hyperexogenous. The diversity of systems and the growing competition is very influential on cultural actors. Like  a  vortex  of  endless,  global  culture must  be  faced  with  an  optimistic attitude. But beside  that,  there  is negligence on  the  toughness of  their own culture. In  this  fast-paced atmosphere of a gap  there was a group of young people who  dared  to  display works with  the  image  of  different  traditions. Serving them is the answer to the advantage of local cultural (ethnic culture). Academic base that is grounded in local culture is essential for the existence of cultural  capital  of  the  nation.  This  exposure  is  only  a  fraction  of  the phenomenon of cultural work. Hopefully their enthusiasm will motivate other young people.